The maternal factors during pregnancy for intrauterine growth retardation: An umbrella review - Jenabi Ensiyeh; Arabzadeh Hoda; Abdoli Sara; Khazaei Salman (Open Medicine)
There is no umbrella review on maternal risk factors associated with intrauterine growth retardation (IUGR). Therefore, we assessed an umbrella review on maternal risk factors during pregnancy for IUGR.